PENGARUH VARIETAS DAN WAKTU PENYIANGAN GULMA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SORGUM (sorgum bicolor L .) moench) - Karisma Str A.G; Cut mulyani; Ainul Mardiah (Jurnal Cakrawala Ilmiah, 2024)
This research aims to determine the effect of varieties and weeding time on the growth and varieties of sorghum plants. This research uses a factorial randomized block design (RAK) with 2 factors, the first factor is the use of varieties (V) with 3 levels, namely V1(numbu), V2(kawali ), V3 (super) and the second factor of weed weeding time (W) with 4 levels, namely W1(7 DAT), W2(14 DAT), W3(21 DAT), W4(28 HST). This research was carried out. This research was carried out in the experimental garden of Samudra University, Langsa City, Aceh Province with an altitude of ± 10 m above sea level. The research was carried out for 4 months which was carried out from June 2022 to September 2022. This research used a Randomized Block Design (RAK) pattern. factorial which consists of 2 factors, the first factor is the use of varieties (V) which consists of 3 levels, namely: V1 = Numbu, V2 = Kawali, V3 = Super. The second factor is weed weeding time (W) which consists of 4 levels, namely: W1 = 7 HST, W2 = 14 HST, and W3 = 21 HST, W4 = 28 HST. The parameters measured were plant height, stem diameter, number of leaves, panicle length, wet panicle weight, dry panicle weight, seed weight per plot